Chronic recurrent transverse myelitis or multiple sclerosis [case report] - Ungureán Aurélia (FUNCTIONAL NEUROLOGY, 1996)
The simultaneous occurrence of multiple sclerosis and transverse myelitis is known in the literature. Apart from the spinal symptoms, other neurological signs of brain involvement are usually found and magnetic resonance imaging (MRI) reveals disseminated foci in the brain. The positive evoked responses, the immunological abnormalities of the cerebrospinal fluid (CSF), and the oligoclonality together prove the presence of multiple sclerosis. In these cases the symptoms of transverse myelitis can separately precede other signs of multiple sclerosis, or appear as a relapse. Recurrent transverse myelitis as an independent entity, with negative MRI and CSF immunology, is an exciting topic in terms of the etiological factors and therapeutic considerations. The view in the literature is that the occurrence of transverse myelitis as an independent entity is rather rare. The present article reports the case of a female patient with recurrent spinal cord signs, and negative MRI and CSF immunology. During a ten-year follow-up observation period, symptoms of multiple sclerosis did not develop. Further studies of such cases are needed in order to clarify the etiological factors, the pathomechanism and the therapeutic considerations relating to this relatively new and probably independent clinical entity.